Interregional relationships in the Russian dairy market: Spatial growth poles - Ilya V. Naumov; Vladislav M. Sedelnikov (Journal of New Economy, 2021)
Significant differentiation between Russian regions in the production and consumption of milk and dairy products hampers the food security. The paper investigates interregional relationships in the indicated processes. Methodologically, the research relies on the regional and spatial economics, in particular on Hirschman’s theory of backward and forward linkages, Perroux’s theory of growth poles, Christaller’s central place theory, Lösch’s theory of spatial organisation of the economy, Friedman’s core-periphery theory, and some others. Using the spatial autocorrelation analysis by Moran procedure and the research of inter-territorial interactions according to Anselin, the authors determine the main regional centers of milk production and consumption, cluster the regions according to the level of dairy production, and specify clusters of closely interconnected regions of Russia on the basis of the identified interregional relationships. The agro-industrial cluster structures functioning in these territories confirm the tightness of the identified interregional cooperative direct and reverse relationships. The four clusters include the Siberian cluster (Novosibirsk, Omsk, Tyumen oblasts, etc.), the Southern cluster (Krasnodar krai, Rostov and Belgorod oblasts, etc.), the Central cluster (Vladimir and Nizhny Novgorod oblasts, Republic of Mordovia, etc.), and the Ural-Volga cluster (Republic of Tatarstan, Sverdlovsk and Nizhny Novgorod oblasts). The results of the study can be useful for researchers involved in the design of spatial strategies, regional programmes and models of socioeconomic development, as well as for regional and municipal authorities implementing the Strategy for the spatial development of the Russian Federation for the period up to 2025.